2004
DOI: 10.2337/diacare.27.8.1904
|View full text |Cite
|
Sign up to set email alerts
|

Excess Hospitalizations, Hospital Days, and Inpatient Costs Among People With Diabetes in Andalusia, Spain

Abstract: OBJECTIVE -The goal of this study was to estimate the excess hospitalizations, hospital days, and inpatient costs attributable to diabetes in Andalusia, Spain (37 hospitals,7,236,459 inhabitants), during 1999 compared with those without diabetes.RESEARCH DESIGN AND METHODS -This study was an analysis of all hospital discharges. Those with an ICD-9-CM code of 250 as either the main or secondary diagnosis were considered to have been admissions of individuals with diabetes. An estimate of costs was applied to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
29
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 24 publications
4
29
0
5
Order By: Relevance
“…2,3 These devices are used at hospitals, health care centers, as well as by patients, which provides them with an essential tool for self-control of their diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 These devices are used at hospitals, health care centers, as well as by patients, which provides them with an essential tool for self-control of their diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…2 The most common chronic complications are coronary heart disease and stroke which constitute about 65% of mortality. 1,4 Meanwhile, complications such as retinopathy, stroke, and diabetic foot are the main causes of disability related to diabetes. 4 In Indonesia, stroke remains the most frequent cause of death.…”
mentioning
confidence: 99%
“…[1][2][3] Previous studies showed that diabetes patients are high risk to suffer from complications in the form of microvascular and macrovascular disorders. Multicentre studies in China and Micronesia which gathered data from outpatients, found that diabetes chronic complications prevalence rate is exceedingly high.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes the results of studies conducted on the prevalence of diabetes in different areas of Iran. The evidences show that the use of health care services in diabetic patients is much higher than many other diseases [12][13][14][15][16][17]. These led to diabetes to be responsible for 11.6% of the world's medical expenses in 2010 varying from 5% to 13% in different countries [1].…”
Section: Introductionmentioning
confidence: 99%